EXPERIMENTAL MONTHLY LONG-RANGE FORECASTS FOR THE UNITED-KINGDOM .2. A REAL-TIME LONG-RANGE FORECAST BY AN ENSEMBLE OF NUMERICAL INTEGRATIONS - Murphy, J; Palmer, T (1986)
The use of an ensemble of integrations for long-range prediction has been studied with a hemispheric version of the Meteorological Office 5-level general circulation model. Some results, showing the potential of the technique, are described. The method is now being used with the global 11-level model to produce real-time long- range forecasts for the long-range forecasting conference in the Synoptic Climatology Branch of the Meteorological Office. Results from the first of these real-time ensemble forecasts are discussed. -Authors